(untitled) (Journal of Partial Differential Equations, 1990)
In this paper we consider the initial-boundary value problem for the higher-order degenerate quasilinear parabolic equation &#8706u(x, t)&#8706t + &#931_|&#945|&#8804M(-1)^|&#945|D^&#945A_&#945(x, t, &#948u, D^mu) = 0 Under some structural conditions for A_&#945(x, t, &#948u, D^mu), existence and uniqueness theorem are proved by applying variational operator theory and Gal&#235rkin method.